The transformation of EU treaty making : the rise of parliaments, referendums and courts since 1950 / Dermot Hodson, Birkbeck College, University of London, Imelda Maher, University College Dublin. - Hodson, Dermot; Maher, Imelda (Cambridge studies in European law and policy., 2018)
Treaty making is a site of struggle between those who claim the authority to speak and act on the international stage. The European Union (EU) is an important test case in this respect because the manner in which the Union and its member states make treaties has shifted significantly over the last six decades. Drawing insights from EU law, comparative constitutionalism and international relations, this book shows how and why parliaments, the people and courts have entered a domain once dominated by governments. It presents qualitative and quantitative evidence on the importance of public trust and political tactics in explaining this transformation of EU treaty making and challenges the idea that EU treaties are too rigid. Analysing legal developments in the EU and each of its member states, this will be essential reading for those who wish to understand the EU's controversial experiment in treaty making and its wider significance.